Comparative analysis of Kirschner wire configurations for fixation of extra-articular proximal hallux fractures: Insights from synthetic composite bone models - Soner Kocak; Bulent Kilic; Mustafa Caliskan; Muhammed Yusuf Afacan; Bora Uzun; Fatih Ertem; Deniz Gulabi; Cemil Erturk (Journal of Orthopaedic Surgery)
Purpose: This study compares the durability and stability of Kirschner wires used in two different configurations for the fixation of extra-articular fractures of the proximal hallux. Methods: Standardized and reproducible extra-articular osteotomy lines were fixed with Kirschner wires arranged in cross and parallel configurations using synthetic composite bone models. These fixed composite bones were assessed under two distinct experimental setups. Measurements recorded included the load causing 2 mm displacement at the osteotomy line, load-to-failure, displacement at failure, and stiffness values. Results: In both experimental setups, the load causing 2 mm displacement, load-to-failure, and failure stiffness values were significantly higher for the cross configuration compared to the parallel configuration. Conversely, the displacement at failure was significantly lower in the cross configuration relative to the parallel configuration. Additionally, the force required to induce a 2 mm displacement in the cross-configuration group exceeded the force exerted on the hallux during normal walking. Conclusion: The results indicate that Kirschner wires applied in a cross configuration offer superior stability and durability for the fixation of proximal hallux fractures compared to the parallel configuration in synthetic composite bone models. To validate these findings and assess clinical outcomes, further research through a prospective randomized controlled trial is recommended.